A Igreja Metodista e sua ação pastoral frente ao fenômeno do envelhecimento populacional brasileiro - Nogueira, Paulo Dias (2009)
Population aging is a worldwide reality. In the case of Brazil, it can be said that this phenomenon has brought new challenges for the government and society as a whole. The Methodist Church, as part of this society, is a community of faith that presents in its documents a pastoral proposal for strong engagement in social issues. Given this, this research aims to analyze the Pastoral Action of the Methodist Church against the phenomenon of Brazilian population aging. For the elaboration of the same it uses two methods of procedure: the historical method, for the first and the second chapters, and the statistical method for the third. The first chapter addresses the concepts and prejudices related to old age and aging; A demographic analysis of the Brazilian population aging is presented. and lastly, I make brief comments about old age in the face of neoliberalism. The second chapter presents a brief history and the conceptualization of terms relevant to the research: Practical Theology, Pastoral, Praxis and Methodist Church. Finally, in the third chapter, we present the analysis and discussion of the results of field research conducted in three churches, whose objective is to assess in their daily lives what has been effectively the Pastoral Action of the Methodist Church in face of the phenomenon of population aging. . In the final considerations of the study, with the research results, some pastoral clues for action with and for the elderly are presented. (AU)